2013
DOI: 10.4142/jvs.2013.14.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal Doppler sonography of uterine blood flow during the first two weeks after parturition in Simmenthal heifers

Abstract: Transrectal Doppler sonography was used to evaluate uterine blood flow during the first two weeks after parturition in six primiparous Simmental cows. The uterine blood flow was evaluated on the day of parturition (Day 0), once daily from Days 1 to 8 and then every other day until Day 14. Blood flow was quantified by determining the diameter (D), the time-averaged maximum velocity (TAMV), the pulsatility index (PI) and the blood flow volume (BFV) of the uterine arteries ipsilateral and contralateral to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
2
17
1
3
Order By: Relevance
“…Previous studies indicated that many factors affect involution, including uterine infections, parity, and seasons (27). One study indicated that suppression of the early resumption of cyclicity improved uterine involution in cows with and without uterine diseases (28). In this study, the time of the first postpartum ovulation was determined to have occurred on approximately the expected day (7,16,22).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies indicated that many factors affect involution, including uterine infections, parity, and seasons (27). One study indicated that suppression of the early resumption of cyclicity improved uterine involution in cows with and without uterine diseases (28). In this study, the time of the first postpartum ovulation was determined to have occurred on approximately the expected day (7,16,22).…”
Section: Discussionmentioning
confidence: 87%
“…This gives implication that the used dose of CTC in this study is satisfactory for controlling bacteria causing endometritis for at least 72 hours. As the rate of drug absorption greatly depends on local blood flow [37], the great fluctuation of the CTC concentration in the serum reported throughout this study may be ascribed to the erratic uterine blood flow during the first 4 postpartum days [38].…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, measurement of cervical diameter, endometrial thickness and assessment of echogenicity of the Herd monitoring to optimise fertility intra-uterine fluid from Days 15 to 21 postpartum predicted subsequent reproductive performance (López-Helguera et al, 2012). Doppler assessment of uterine blood flow and involution postpartum are still in their infancy and more data comparing animals with and without subsequent disease are needed before the clinical use of this procedure can be assessed (Heppelmann et al, 2013). The use of cytology and ultrasonography to diagnose and predict outcome of clinical and sub-clinical uterine disease are still being investigated by several groups.…”
Section: Smith Oultram and Dobsonmentioning
confidence: 99%